Low‐Altitude Ion Heating, Downflowing Ions, and BBELF Waves in the Return Current Region. Issue 4 (21st April 2018) - Shen, Yangyang; Knudsen, David J.; Burchill, Johnathan K.; Howarth, Andrew D.; Yau, Andrew W.; Miles, David M.; James, H. Gordon; Perry, Gareth W.; Cogger, Leroy
Abstract: Heavy (O + ) ion energization and field‐aligned motion in and near the ionosphere are still not well understood. Based on observations from the CAScade, Smallsat and IOnospheric Polar Explorer (CASSIOPE) Enhanced Polar Outflow Probe at altitudes between 325 km and 730 km over 1 year, we present a statistical study (24 events) of ion heating and its relation to field‐aligned ion bulk flow velocity, low‐frequency waves, and field‐aligned currents. The ion temperature and field‐aligned bulk flow velocity are derived from 2‐D ion velocity distribution functions measured by the suprathermal electron imager (SEI) instrument. Consistent ion heating and flow velocity characteristics are observed from both the SEI and the rapid‐scanning ion mass spectrometer instruments. We find that transverse O + ion heating in the ionosphere can be intense (up to 4.5 eV), confined to very narrow regions (∼2 km across B), is more likely to occur in the downward current region and is associated with broadband extremely low frequency (BBELF) waves. These waves are interpreted as linearly polarized perpendicular to the magnetic field. The amount of ion heating cannot be explained by frictional heating, and the correlation of ion heating with BBELF waves suggests that significant wave‐ion heating is occurring and even dominating at altitudes as low as 350 km, a boundary that is lower than previously reported. Surprisingly, the majority of these heating events (17 out 24) are associated with core ion downflows rather than upflows. This may be explained by a downward pointing electric field in the low‐altitude return current region. Plain Language Summary: We present the first statistical observations (24 events) of low‐altitude (325–730 km) ion heating using both plasma and wave measurements from the CASSIOPE Enhanced Polar Outflow Probe satellite. We report the first observations of strong ion heating (up to 4.5 eV, or 50, 000 K) down to 350 km altitude. These observations indicate that wave‐particle interaction is important in the ion energization process at low altitudes. Unexpectedly, the majority of the ion heating events are correlated with ion downflows rather than upflows. This may be explained by downward pointing electric fields at ionospheric altitudes associated with regions of downward electric currents. Key Points: Statistical observations of low‐energy O + ion heating and low‐frequency waves suggest strong wave‐ion heating at altitudes as low as 350 km Majority of the ion heating events are associated with core ion downflows rather than upflows Downward pointing electric fields associated with physical processes in the low‐altitude return current region may explain the downflows